PENERAPAN MODEL PEMBELAJARAN COOPERATIF TIPE THINK PAIR SHARE (TPS) UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELASV SD NEGERI 011 PEMATANG INDAH KECAMATAN KELAYANG KABUPATEN INDRAGIRI HULU - Halimah Halimah; Damanhuri Daud; Jesi Alexander Alim (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstrack : This research at performs since its low usufruct IPA'S studying student brazes v SDN 011 Causeway Is Beautiful that haven't reached KKM (Minimum thoroughness criterion) one that is established which is 65. This appears from peneletian's startup data of 14 students which reach points according to KKM as much 6 students with averagely brazes 62,5. Its low is yielding studies it at causes since teacher be still dominate deep learning so student involvement in learning becomes less active. Base about problem research do that action brazes with learnings model implement kooperatif Think Pair Share's type (TPS). This research intent to increase IPA'S studying result student brazes v SDN 011 Causeway Is Beautiful School Years 2014 / 2015. This research is executed deep two cycles, whereabouts on each cycle it consisting of two-time appointment gazes to show face and once daily dry run. With be applied Model Kooperatif's Learning Think Pair Share's Type (TPS), therefore gets to increase IPA'S studying result student brazes v SDN 011 Causeway Is Beautiful on solar Structured material and earth and soiled forming process. It can at see of thoroughness result studies individual and klasikal which gotten by student on base score which is with thoroughness percentage 42,85%, with average 62,5, worked up on i. cycle with thoroughness percentage 71,42% by average 70. Worked up again on cycle II.which is with thoroughness percentage 100%. Learned yielding step-up student gets at see on base score goes to i. UH which is with increasing percentage 10,71% and on base score goes to UH II. which is with increasing percentage 22,21%. Activity learns first cycle with percentage average 81,24% worked up as 94,79% on second cycle. Student activity on first cycle with percentage average 68,73% worked up as 92,18% on second cycle. Of acquired data as above as gets to be known that pass through learning model Implement kooperatif Think Pair Share's type (TPS), can increase IPA'S studying result student brazes v SDN 011 Causeway Is Beautiful.Key word: TPS, IPA'S Learned result